PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Ismi Norisa; Riana R. Dewi; Anita Wijayanti (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Tax avoidance is one of the methods used by taxpayers in paying their tax obligations by reducing the amount of tax owed. This study aims to determine and analyze the effect of profitability, leverage, liquidity, and sales growth on tax avoidance. The research was conducted quantitatively using a sample of coal sub-sector mining companies listed on the IDX for the 2016-2020 period. With a sample of 24 coal companies. The sample method uses purposive sampling technique so that a sample of 10 companies is produced that meets the criteria. Data collection techniques using documentation techniques, while the analytical method used is multiple linear regression analysis. Simultaneously the results of this study indicate that the variables of profitability, leverage, liquidity, and sales growth have an effect on tax avoidance. While partially the results of this study indicate that profitability has no effect on tax avoidance, leverage has no effect on tax avoidance, liquidity has no effect on tax avoidance, and sales growth has no effect on tax avoidance.